1983
DOI: 10.1002/jcu.1870110602
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of liver volume by ultrasound and computed tomography

Abstract: A morphometric method to calculate liver volumes from transverse sections is evaluated (point-integrating method). In the first part of the study, 10 liver specimens were investigated by computed tomography (CT) and ultrasound (US); the calculated volumes were compared to the volumes obtained by water displacement of the organs. While CT showed an ideal agreement (r = 0.994), volumes calculated from US sections correlated less well (percentage differences from +12.5% to -9%, r = 0.915). In the second part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 10 publications
0
28
0
2
Order By: Relevance
“…There have been a few attempts in the past to use a primitive form of 3D ultrasound, where the position of each B-scan is recorded manually, to measure liver volume [11,36,62,153]. The earliest of these used a freehand scanning technique [153], although the accuracy of the volume measurements was limited by the large number of hand calculations and inaccurate B-scan localisation.…”
Section: Visualisation Of Implicit Surfacesmentioning
confidence: 99%
“…There have been a few attempts in the past to use a primitive form of 3D ultrasound, where the position of each B-scan is recorded manually, to measure liver volume [11,36,62,153]. The earliest of these used a freehand scanning technique [153], although the accuracy of the volume measurements was limited by the large number of hand calculations and inaccurate B-scan localisation.…”
Section: Visualisation Of Implicit Surfacesmentioning
confidence: 99%
“…[1][2][3][4] For patients undergoing major hepatic resection, the likelihood of post -hepatectomy liver failure is three times higher in patients who are left with < 25% of their initial liver volume compared to those who are left with ≥ 25% of their initial liver volume. [5] Mortality and morbidity rates for major hepatic resection have been reported to be as high as 30% with post hepatic liver failure being the major cause.…”
Section: Introductionmentioning
confidence: 99%
“…However, whole-hepatic enlargement is proportional to the severity of the metabolic syndrome, and various imaging methodologies can be used for the estimation of liver volume. 15,16 We have recently introduced an ultrasound technique that measures the hepatic left lobe volume (HLLV), calculated by the ellipsoid formula, and we have shown that HLLV is tightly correlated to, and thus an excellent indicator of, visceral adiposity. 17 Treatment of obesity is based upon low-calorie diets, behavioral modifications and physical activity, the pharmacological treatment being considered as further approach.…”
Section: Introductionmentioning
confidence: 99%